Beyond the "Choosing wisely": a possible attempt. Issue 1 (December 2016) - Bernardini, Roberto; Ricci, Giampaolo; Cipriani, Francesca; Civitelli, Flavio; Indinnimeo, Luciana; Minasi, Domenico; Terracciano, Luigi; Duse, Marzia
Abstract Since the fundamental principles of the medical profession were clearly defined in a physician charter in 2002, special considerations have been expressed about the adequate distribution of health care resources taking in account the individual patient needs to optimize the health care service. The correct application of procedures represents a key point in order to reach the appropriateness of care, that means to avoid unnecessary or inappropriate procedures as well as the underutilization of the necessary procedures. In this context, the Choosing wisely campaign have been widely used and disclosed and even the Italian Society of Pediatric Allergology and Immunology - SIAIP has been working to make recommendations in order to ensure the appropriateness of care in the field of allergy and optimize the use of health care resources.